2019
DOI: 10.1186/s12951-019-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion resistance of zinc-containing nanowires-modified titanium surface under exposure to oxidizing microenvironment

Abstract: Titanium (Ti) and its alloys as bio-implants have excellent biocompatibilities and osteogenic properties after modification of chemical composition and topography via various methods. The corrosion resistance of these modified materials is of great importance for changing oral system, while few researches have reported this point. Recently, oxidative corrosion induced by cellular metabolites has been well concerned. In this study, we explored the corrosion behaviors of four common materials (commercially pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Therefore, the potential of Zn 2+ loaded scaffolds to regulate M s polarization for tissue engineering has been gradually explored (Table 2 ). Zhu et al [ 28 ] and Chen et al [ 29 ] observed that Zn-decorated Ti/TiO 2 surfaces induced the M2 state of M s and had better osseointegration or bone regeneration capacity. Additionally, Zn-loaded silica-nanofibrous polymers attained the lowest M1/M2 ratio of M s and achieved the greatest efficiency for bone and vascular regeneration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the potential of Zn 2+ loaded scaffolds to regulate M s polarization for tissue engineering has been gradually explored (Table 2 ). Zhu et al [ 28 ] and Chen et al [ 29 ] observed that Zn-decorated Ti/TiO 2 surfaces induced the M2 state of M s and had better osseointegration or bone regeneration capacity. Additionally, Zn-loaded silica-nanofibrous polymers attained the lowest M1/M2 ratio of M s and achieved the greatest efficiency for bone and vascular regeneration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, under the modulation of the microenvironment created by the implanted scaffolds, M s undergo polarization to either the anti-inflammatory (M2 subtype) or pro-inflammatory (M1 subtype) phenotype and subsequently release a wide series of bioactive molecules, leading to active regeneration of bone or induction of persistent inflammation, respectively [ 26 , 27 ]. Recently, several studies proposed that Zn-decorated membranes or Ti/TiO 2 implants could intensively induce the polarization of M s toward the anti-inflammatory phenotype (M2) [ 28 – 30 ]. Similarly, Zn 2+ deficiency aggravated inflammation, reduced the numbers of M2-polarized M s and increased the numbers of M1-polarized M s [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many new types of titanium alloys with high-quality performance have been invented through in-depth research on titanium alloy preparation ( Zhang C. et al, 2017 ; Wang et al, 2018 ; Attarilar et al, 2019a , b ; Hafeez et al, 2019 ) and optimization of titanium alloy composition ( Liu et al, 2015a ; Wang et al, 2016 ; Rabadia et al, 2019a , b ). These new titanium alloys show outstanding application value in mechanical properties ( Guo et al, 2013 ; Wang et al, 2015 ; Jawed et al, 2019 ; Hafeez et al, 2020 ), corrosion resistance ( Lee et al, 2015 ; Zhu W.Q. et al, 2019 ; Malhotra et al, 2020 ), and osteogenic action ( Zhu et al, 2016 ; Li H.F. et al, 2019 ; Lei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their metabolites reduced the local pH value in a short time, destroyed the oxide film on the surface of Ti, and caused corrosion and release of Ti ions (Xu, Yu, Chen, Zhang, & Qiu, 2020;Zhang et al, 2013). Besides microbial corrosion, many corrosion types exist around the Ti implant, such as stress corrosion, osteoclast corrosion, oxidative corrosion, pitting corrosion, fretting corrosion, and so on, which affect and promote each other, eventually leading to the release and aggregation of Ti ions (Cadosch et al, 2010;Golvano, Garcia, Conde, Tato, & Aginagalde, 2015;Zhu et al, 2019). Excessive Ti ions may cause adverse biological reactions.…”
Section: Introductionmentioning
confidence: 99%